Culture and economy in the Indian diaspora - Parekh, Bhikhu C.; Singh, Gurharpal; Vertovec, Steven (Transnationalism., 2003)
Examines the Indian diaspora in Mauritius, South Africa, Malaysia, Sri Lanka, the Middle East, Trinidad, Australia, the US, Canada and the UK and the core issues of demography, economy, culture and future development.